Synthesis, Characterization, Molecular Modeling, Antimicrobial and DNA Binding Studies of Cobalt(II) Complexes of 2,3-(Diimino-4'-antipyrinyl)butane with Varying Counter Ions - Anila, B.N.; Muraleedharan Nair, M.K.; Sreedharan, Jisha; Sylas, V.P. (Asian Journal of Chemistry, 2016)
The synthesis and characterization of perchlorate, nitrate, chloride, bromide and iodide complexes of cobalt(II) with a new Schiff base ligand 2,3-(diimino-4¢-antipyrinyl)butane prepared from 4-aminoantipyrine and 2,3-butanedione have been done by elemental analysis, electrical conductance in non-aqueous solvents, infrared and electronic and 1H NMR spectra as well as thermogravimetry. The UV-visible, magnetic susceptibility and ESR spectral data suggest an octahedral geometry around the central metal ion in chloro and bromo complexes and a tetrahedral geometry around the central metal ion for perchlorate, nitrate and iodide complexes. The molecular modeling of the proposed structure is in agreement with the above mentioned structure. Biological screening analyses of the ligands and the cobalt(II) complexes reveals that the Schiff base and its cobalt(II) complexes show significant activity against microorganisms. Binding studies of Co(II) complexes with calf thymus DNA (CT DNA) were studied by spectral methods such as absorption spectroscopy through the ethidium bromide (EB) displacement technique and viscosity measurements. The results obtained indicate that the complexes bind to DNA via intercalation.